Creation Of Energy Field Terms by Lexical-Semantic Method (Texas Journal of Philology, Culture and History, 2023)
This article provides general information about the formation of terms used in the field of energy by the lexical-semantic method, and their place in the field of general terminology, in particular, about the verbal composition of this field as a field of science. highlighted on an analytical basis